Extraordinary tunable dynamic range of electrochemical aptasensor for accurate detection of ochratoxin A in food samples - Lin Cheng; Hao Qu; Jun Teng; Li Yao; Feng Xue; Wei Chen (Food Science and Human Wellness)
We report the design of a sensitive, electrochemical aptasensor for detection of ochratoxin A (OTA) with an extraordinary tunable dynamic sensing range. This electrochemical aptasensor is constructed based on the target induced aptamer-folding detection mechanism and the recognition between OTA and its aptamers results in the conformational change of the aptamer probe and thus signal changes for measurement. The dynamic sensing range of the electrochemical aptasensor is successfully tuned by introduction of free assistant aptamer probes in the sensing system. Our electrochemical aptasensor shows an extraordinary dynamic sensing range of 11-order magnitude of OTA concentration from 10−8 to 102 ng/g. Of great significance, the signal response in all OTA concentration ranges is at the same current scale, demonstrating that our sensing protocol in this research could be applied for accurate detections of OTA in a broad range without using any complicated treatment of signal amplification. Finally, OTA spiked red wine and maize samples in different dynamic sensing ranges are determined with the electrochemical aptasensor under optimized sensing conditions. This tuning strategy of dynamic sensing range may offer a promising platform for electrochemical aptasensor optimizations in practical applications.